2019
DOI: 10.3390/ijms20236017
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Clinical Drug Testing in 2D and 3D Human In Vitro Models of Glioblastoma Incorporating Non-Neoplastic Astrocytes: Tunneling Nano Tubules and Mitochondrial Transfer Modulates Cell Behavior and Therapeutic Response

Abstract: The role of astrocytes in the glioblastoma (GBM) microenvironment is poorly understood; particularly with regard to cell invasion and drug resistance. To assess this role of astrocytes in GBMs we established an all human 2D co-culture model and a 3D hyaluronic acid-gelatin based hydrogel model (HyStem™-HP) with different ratios of GBM cells to astrocytes. A contact co-culture of fluorescently labelled GBM cells and astrocytes showed that the latter promotes tumour growth and migration of GBM cells. Notably, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 90 publications
0
48
0
Order By: Relevance
“…Similarly, another study hypothesizes that astrocytes in TME behave like microglia by reducing cancer sensitivity to drugs and interactions between astrocytes and GB cells could be associated with increased growth and invasion of the tumor [96]. To confirm this, it was demonstrated that the direct contact between 3D co-culture of astrocytes and GB cells enhances glioblastoma formation [97]. More in detail, the authors of this study suggested that astrocytes may rescue the damaged target cancer cells transferring organelles along tunneling nanotubes.…”
Section: Co-cultures Of Cerebral Organoidsmentioning
confidence: 60%
“…Similarly, another study hypothesizes that astrocytes in TME behave like microglia by reducing cancer sensitivity to drugs and interactions between astrocytes and GB cells could be associated with increased growth and invasion of the tumor [96]. To confirm this, it was demonstrated that the direct contact between 3D co-culture of astrocytes and GB cells enhances glioblastoma formation [97]. More in detail, the authors of this study suggested that astrocytes may rescue the damaged target cancer cells transferring organelles along tunneling nanotubes.…”
Section: Co-cultures Of Cerebral Organoidsmentioning
confidence: 60%
“…Reaserches have further elucidated the potential mechanism of conventional antidepressants therapy for GBM. By targeting the respiratory chain complex III and changing membrane potential, the tricyclics antidepressants mentioned above induce mitochondria-mediated apoptosis of malignant glioma cells, activate the intrinsic pathway of cytochrome-C release and caspase-3 dependent apoptosis process, and finally results in glioma cell death ( 106 112 ). It is worth mentioning that previous studies have also indicated that the anticoagulant ticlopidine synergized with imipramine to induce the death of human glioma cell lines and primary mouse glioma cells ( 98 , 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used culture media for spheroids are Eagle’s minimal essential medium (EMEM), Dulbecco modified Eagle’s minimal essential medium (DMEM) and Roswell Park Memorial Institute medium (RPMI) supplemented with penicillin/streptomycin and fetal bovine serum (FBS). Human serum has also been used to better mimic the natural microenvironment of cancer cells [ 32 , 33 ]. The majority of the existing GBM cell lines (U-87MG, U-105MG, U-118MG, U-138MG, U-178MG, U-251MG, U-343MG, U-373MG, U-1231MG, BMG-1, T98G, A172, SNB-19, ACBT, M059J, LN-229, Hu197, and LN-18) are able to form spheroids except the U-343MG cell line [ 7 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Sphere-based Modelsmentioning
confidence: 99%